The 2016 Kumamoto Earthquakes: Cascading Geological Hazards and Compounding Risks - Goda, Katsuichiro; Campbell, Grace; Hulme, Laura; Ismael, Bashar; Ke, Lin; Marsh, Rebekah; Sammonds, Peter; So, Emily; Okumura, Yoshihiro; Kishi, Nozar; Koyama, Maki; Yotsui, Saki; et al. (Frontiers in Built Environment, 2016)
A sequence of two strike-slip earthquakes occurred on 14 and 16 April 2016 in the intraplate region of Kyushu Island, Japan, apart from subduction zones, and caused significant damage and disruption to the Kumamoto region. The analyses of regional seismic catalog and available strong motion recordings reveal striking characteristics of the events, such as migrating seismicity, earthquake surface rupture, and major foreshock-mainshock earthquake sequences. To gain valuable lessons from the events, a UK Earthquake Engineering Field Investigation Team (EEFIT) was dispatched to Kumamoto, and earthquake damage surveys were conducted to relate observed earthquake characteristics to building and infrastructure damage caused by the earthquakes. The lessons learnt from the reconnaissance mission have important implications on current seismic design practice regarding the required seismic resistance of structures under multiple shocks and the seismic design of infrastructure subject to large ground deformation. The observations also highlight the consequences of cascading geological hazards on community resilience. To share the gathered damage data widely, geo-tagged photos are organized using Google Earth and the kmz file is made publicly available.